Max Gobbo e la riscrittura fantastica di un periodo rinascimentale - Zangrilli, Franco (Italianistica Debreceniensis, 2017)
The paper examines thè characteristics of Max Gobbo’s writing in his fantasy novel Alasia - The Iron Maiden. The novel is set in a dystopian XVI century Italy infested by demons, vampires and other strange creatures. The novel unfolds in a clear and flowing prose, supported by a simple and effective writing, expressing thè complexity of a world of darkness, in thè hands of devils. It is full of suspense, of comings and goings, of mythical evocations, as of dramatic moments and a humorous multitone irony.